![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
c)\(C=5+\sqrt{-4x^2-4x}\)
\(C=5+\sqrt{1-\left(4x^2+4x+1\right)}\)
\(C=5+\sqrt{1-\left(2x+1\right)^2}\)
Ta có: \(-\left(2x+1\right)^2\le0\)
\(\sqrt{1-\left(2x+1\right)^2}\le1\)
\(\sqrt{1-\left(2x+1\right)^2}+5\le6\Leftrightarrow C\le6\)
Vậy \(C_{max}=6\) khi \(2x+1=0\Leftrightarrow x=-\frac{1}{2}\)
f) \(F=\sqrt{4x^2-4x+1}+\sqrt{4x^2-12x+9}\)
\(F=\sqrt{\left(2x-1\right)^2}+\sqrt{\left(2x-3\right)^2}\)
\(F=\left|2x-1\right|+\left|3-2x\right|\ge\left|2x+1+3-2x\right|=4\)
\(F_{min}=4\) khi \(\left(2x-1\right)\left(3-2x\right)\ge0\Leftrightarrow\frac{1}{2}\le x\le\frac{3}{2}\)
Mấy còn lại tương tự =)))
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\sqrt{16x+16}-\sqrt{9x+9}+\sqrt{4x+4}+\sqrt{x+1}=16\)
\(\Leftrightarrow4\sqrt{x+1}-3\sqrt{x+1}+2\sqrt{x+1}+\sqrt{x+1}=16\)
\(\Leftrightarrow4\sqrt{x+1}=16\)
\(\Leftrightarrow\sqrt{x+1}=4\)
<=> x + 1 = 16
<=> x = 15 (nhận)
~ ~ ~
\(\sqrt{4x+20}-3\sqrt{5+x}+\dfrac{4}{3}\sqrt{9x+45}=6\)
\(\Leftrightarrow2\sqrt{x+5}-3\sqrt{x+5}+4\sqrt{x+5}=6\)
\(\Leftrightarrow3\sqrt{x+5}=6\)
\(\Leftrightarrow\sqrt{x+5}=2\)
<=> x + 5 = 4
<=> x = - 1 (nhận)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(1-4x\ge0\Leftrightarrow x\le\frac{1}{4}\)
b/ \(3-4x\ne0\Leftrightarrow x\ne\frac{3}{4}\)
c/\(2x-2< 0\Leftrightarrow x< 1\)
d/ \(\left\{{}\begin{matrix}4x+2\ne0\\1+3x\ge0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x\ne\frac{-1}{2}\\x\ge\frac{-1}{3}\end{matrix}\right.\Leftrightarrow x\ge\frac{-1}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a/ \(1-4x\ge0\Rightarrow x\le\frac{1}{4}\)
b/\(3-4x\ne0\Rightarrow x\ne\frac{3}{4}\)
c/ \(2x-2< 0\Rightarrow x< 1\)
d/ \(\left\{{}\begin{matrix}4x+2\ne0\\1+3x\ge0\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x\ne-\frac{1}{2}\\x\ge-\frac{1}{3}\end{matrix}\right.\) \(\Rightarrow x\ge-\frac{1}{3}\)
Cách 1:
\(\sqrt{4x-1}+\sqrt{4x^2-1}=1\)
\(\Leftrightarrow\left(\sqrt{4x-1}-1\right)+\sqrt{4x^2-1}=0\)
\(\Leftrightarrow\frac{4x-2}{\sqrt{4x-1}+1}+\sqrt{\left(2x-1\right)\left(2x+1\right)}=0\)
\(\Leftrightarrow\sqrt{2x-1}\left(\frac{2\sqrt{2x-1}}{\sqrt{4x-1}+1}+\sqrt{2x+1}\right)=0\)
\(\Leftrightarrow\sqrt{2x-1}=0\)
\(\Leftrightarrow x=\frac{1}{2}\)
Cách 2:
Điều kiện: \(x\ge\frac{1}{2}\)
Ta có:
\(VT=\sqrt{4x-1}+\sqrt{4x^2-1}\ge\sqrt{4.\frac{1}{2}-1}+\sqrt{4.\left(\frac{1}{2}\right)^2-1}=1=VP\)
Dấu = xảy ra khi \(x=\frac{1}{2}\)